Exegetical Method of Bint al-Shāṭiʾ’s al-Tafsīr al-bayānī – li'l- Qurʼān al-Karīm - An Analytical Assessment - Musferah Mehfooz; Ayesha Rafiq (Pakistan Journal of Islamic Research)
A progressive Muslim thinker, Egyptian scholar, and a woman representing a minority until her time in Qurʼānic studies, ʿĀʾisha ʿAbd al-Raḥmān, widely known by her penname Bint al-Shāṭiʾ (1912-1998), had contributed to introduce a modern outlook in the realm of the interpretation of the Qurʿān. Bint al-Shāṭiʾ had devoted herself to the interpretation of the Qurʿān through the use of a literary approach. In fact, the beginnings of modern literary tafsīr have been traced back to Muḥammad ʿAbduh’s (1849–1905) critical edition of Asrār al-balāgha and Dalāʾil al-iʿjāz, the two major works of the classical philologist and rhetorician ʿAbd al-Qāhiral-Jurjānī (d. 471/1078). The direct influence of Muḥammad ʿAbduh’s ideas has traces in the work of both al-Khūlī and Bint al-Shāṭiʾ. Bint al-Shāṭiʾ had advocated and applied an approach developed by her teacher and husband Amīn al-Khūlī (1895–1966), who had a fundamental influence on her academic and intellectual journey. Although she had written on only 14 surahs in the last part of the Qurʿān but al-Tafsīr al-bayānī Iil- Qurʼān al-Karīm (The Rhetorical Interpretation of the Qurʿān) is the most important of her works on Qurʿān to date. The purpose of this study is to focus on Bint al-Shāṭiʾ’s stylistic beauty and literary approach in her exegesis of Qurʿān and specifically her interpretation about rhetorical inimitability which is further assessed in the light of three particular domains ie; the openings of Qurʿānic chapters and the secret of the letters, the case of synonyms and Oaths of Qurʿān, which are extracted from her al-Tafsīr al-bayānī - Iil-Qurʼān al-Karīm.